Three local plants adapt to ecological restoration of abandoned lead-zinc mines through assembly of rhizosphere bacterial communities - Gao, Wei; Chen, Shuyi; Yu, Xin; Chen, Sumin; Wan, Caijing; Wang, Ying; Wu, Peng; Li, Qiang (Frontiers in Microbiology, 2025)
IntroductionThe plant restoration and ecological restoration of lead-zinc mines are very important.MethodsIn this study, we used three local plants to carry out ecological restoration of abandoned lead–zinc mining areas and detected the adaptive mechanisms of soil bacterial diversity and function during the ecological restoration of lead–zinc mines through 16S rRNA sequencing.ResultsThe results revealed that lead-zinc mining significantly reduced the soil bacterial diversity, including the Shannon, Simpson, and observed species indices, whereas the planting of the three ecological restoration plants restored the soil microbial diversity to a certain extent, leading to increases in the Shannon index and Observed species indices. Mining activities significantly reduced the abundances of RB41 and Bryobacter in the bulk soil compared with those in the nonmining areas, whereas the three ecological restoration plants increased the abundances of RB41 and Bryobacter in the rhizosphere soil compared with those in the bulk soil in the mining areas. Following the planting of the three types of ecologically restored plants, the soil bacterial community structure partially recovered. In addition, different plants have been found to have different functions in the lead-zinc ecological restoration process, including iron complex transport system-permitting proteins and ATP binding cassettes.DiscussionThis study confirms for the first time that plants adapt to the remediation process of abandoned lead-zinc mines by non-randomly assembling rhizosphere bacterial communities and functions, providing a reference for screening microbial remediation bacterial resources and plant microbe joint bioremediation strategies for lead-zinc mines.